\(\left(\frac{1}{1.2}+\frac{1}{2.3}+\frac{1}{3.4}+..+\frac{1}{49.50}\right)x=\frac{49}{50}\)
\(\left(1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+...+\frac{1}{49}-\frac{1}{50}\right)x=\frac{49}{50}\)
\(\left(1-\frac{1}{50}\right)x=\frac{49}{50}\)
\(\frac{49}{50}x=\frac{49}{50}\)
\(x=\frac{\frac{49}{50}}{\frac{49}{50}}\)
\(x=1\)
Vậy \(x=1\)
Gọi A=1/1.2+1/2.3+1/3.4+...+1/49.50
A=1-1/2+1/2-1/3+1/3-1/4+...+1/49-1/50
A=1-1/50
A=49/50
Viết lại ta có: (1/1.2+1/2.3+1/3.4+...+1/49.50)x=49/50
49/50x=49/50
=> x=1
\(\left(\frac{1}{1.2}+\frac{1}{2.3}+\frac{1}{3.4}+...+\frac{1}{49.50}\right)\cdot x=\frac{49}{50}\)
\(\left(1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{49}-\frac{1}{50}\right)\cdot x=\frac{49}{50}\)
\(\left(1-\frac{1}{50}\right)\cdot x=\frac{49}{50}\)
\(\frac{49}{50}\cdot x=\frac{49}{50}\)
\(\Rightarrow x=1\)